Modification of PCL Scaffolds by Reactive Magnetron Sputtering: A Possibility for Modulating Macrophage Responses; ACS Biomaterials Science & Engineering; Vol. 6, iss. 7 - Stankevich K. S. Ksenia Sergeevna; Kudryavtseva V. L. Valeriya Lvovna; Bolbasov E. N. Evgeny Nikolaevich; Shesterikov E. V. Evgeny Viktorovich; Larionova I. V. Irina; Shapovalova E. Elena; Domracheva L. V. Liubov Vladimirovna; Volokhova A. A. Apollinariya Aleksandrovna; Kurzina I. A. Irina Aleksandrovna; Zhukov Yu. M. Yuriy Mikhaylovich; Malashicheva A. B. Anna Borisovna; Kzhyshkovska Yu. G. Yuliya Georgievna; et al. (2020, 2020)
Title screen